2022
DOI: 10.1029/2021jg006659
|View full text |Cite
|
Sign up to set email alerts
|

Land Management Explains the Contrasting Greening Pattern Across China‐Russia Border Based on Paired Land Use Experiment Approach

Abstract: The greening of the Earth over the last decades is predominantly indicated by the enhancements of leaf area index (LAI). Quantifying the relative contribution of multiple determinants, especially changes in climate and in land management changes (LMC), remains an arduous challenge. To solve this problem, we develop a simple yet novel data‐driven method, called the Paired Land Use Experiment (PLUE), for mesoscale analysis. Using PLUE, we analyze vegetation development of the Sanjiang Plain, a transboundary plai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…One of the most typical is the inclusion of critical processes. Using statistical methods based on remote sensing, the extensive impacts of land management on vegetation from global to regional scales have been further identified and emphasized (Chen et al, 2019a;Chen et al, 2022a;2022b). However, due to the complexity of the management process and the lack of management data, although some DGVMs have made efforts, the characterization of the management process by the model remains unfortunate, which may require more theoretical and mechanistic research.…”
Section: Uncertainty Of Gpp Simulated By Dgvmmentioning
confidence: 99%
“…One of the most typical is the inclusion of critical processes. Using statistical methods based on remote sensing, the extensive impacts of land management on vegetation from global to regional scales have been further identified and emphasized (Chen et al, 2019a;Chen et al, 2022a;2022b). However, due to the complexity of the management process and the lack of management data, although some DGVMs have made efforts, the characterization of the management process by the model remains unfortunate, which may require more theoretical and mechanistic research.…”
Section: Uncertainty Of Gpp Simulated By Dgvmmentioning
confidence: 99%
“…A large number of research results showed that the currently widely used machine learning GPP data set (FLUXCOM_GPP) cannot reproduce the long‐term trend and interannual variation of GPP (Jung et al., 2020; Wang et al., 2021; Zhang et al., 2017; Zheng et al., 2020), and which was contrary to the currently recognized significant greening from regional to global scales (Chen et al., 2022; Piao et al., 2020; Yuan et al., 2014). As illustrated above, GPP interannual trend of ECGC_GPP (0.21 Pg C yr −2 ) was comparable to other LUE models and was much larger than ML‐based FLUXCOM_GPP.…”
Section: Discussionmentioning
confidence: 97%